Analisis Distorsi Berbasis Metode Elemen Hingga Pada Proses Pengelasan Kampuh U dan V - Erikman, Erikman; Gunawan, Yuspian; Aksar, Prinob (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2022)
The purpose of the study is to find out the influence of the type of welding on deformation produced by using the element method up to through ansys software. The material used in this study is AlSl 4130 steel material the process of connecting metal or distributing temperature into the connection material is carried out using ansys software with camphor used campuh U and V. The temperature given to the material is 1500°C. The results of the largest deformation research in the U camp are 0.00074711 m while in camphor V the total deformation formed from the welding temperature given is 0.00034381 m. The total difference in deformation formed in each camp is caused by the concentration of temperature that occurs in the material caused by the amount of temperature filling in the camp.keywords: Deformation, welding camp, temperature distribution